2014
DOI: 10.1007/s00203-014-1053-4
|View full text |Cite
|
Sign up to set email alerts
|

An essential role of a ferritin-like protein in acid stress tolerance of Listeria monocytogenes

Abstract: The expression of ten genes of Listeria monocytogenes previously identified as penicillin G-inducible was transcriptionally analyzed in the presence of 0.5 M KCl, pH 5.0 and 42 °C. This study revealed that all the genes are upregulated by osmotic stress, seven by acid stress and four by temperature stress conditions. The contribution of a gene encoding a ferritin-like protein (fri), a two-component phosphate-response regulator (phoP) and an AraC/XylS family transcription regulator (axyR) to temperature, acid a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 25 publications
1
10
0
Order By: Relevance
“…The results obtained in the present study confirm this, since the fur gene was downregulated, and, consequently, the fri gene was upregulated in the presence of EOBp. A recent study demonstrated that the cell-envelope stress response in L. monocytogenes is linked to the osmotic stress response, confirming the results obtained in the present work, because active terpenes compounds present in EOBp act by binding the cell membrane of microorganisms (Milecka et al 2015). Several studies suggest that Fri has a global impact on the L. monocytogenes regulatory network (Dussurget et al 2005;Olsen et al 2005), and this protein is also a mediator of beta-lactam tolerance and resistance to antibiotics such as cephalosporins (Krawczyk-Balska et al 2012).…”
Section: Transcriptomic Analysissupporting
confidence: 91%
“…The results obtained in the present study confirm this, since the fur gene was downregulated, and, consequently, the fri gene was upregulated in the presence of EOBp. A recent study demonstrated that the cell-envelope stress response in L. monocytogenes is linked to the osmotic stress response, confirming the results obtained in the present work, because active terpenes compounds present in EOBp act by binding the cell membrane of microorganisms (Milecka et al 2015). Several studies suggest that Fri has a global impact on the L. monocytogenes regulatory network (Dussurget et al 2005;Olsen et al 2005), and this protein is also a mediator of beta-lactam tolerance and resistance to antibiotics such as cephalosporins (Krawczyk-Balska et al 2012).…”
Section: Transcriptomic Analysissupporting
confidence: 91%
“…; Milecka et al . ). Susceptibility studies revealed that a knockout of gene fri resulted in a two‐fold increase in sensitivity to cephradine and cefalotin and further analysis demonstrated that under β ‐lactam pressure Fri is required to maintain proper level of expression of the dlt operon, which is responsible for d ‐alanylation of cell wall teichoic acids, thus providing an appropriate net charge of the cell wall (Krawczyk‐Balska et al .…”
Section: Regulatory Proteins Involved In the Resistance Of Listeria Mmentioning
confidence: 97%
“…Fri of L. monocytogenes is not a sensu stricto regulator protein; however, in the fri mutant strain significant changes in the content of the global regulators anti-sigma B factor (RsbW) and catabolite control protein A (CcpA) were observed, thus suggesting that Fri has a global impact on the L. monocytogenes regulatory network . Fri was shown to contribute to virulence, and mediate the resistance of L. monocytogenes to iron-starvation, cold-and heat-shock, oxidative and low pH stress Olsen et al 2005;Milecka et al 2015). Susceptibility studies revealed that a knockout of gene fri resulted in a two-fold increase in sensitivity to cephradine and cefalotin and further analysis demonstrated that under b-lactam pressure Fri is required to maintain proper level of expression of the dlt operon, which is responsible for D-alanylation of cell wall teichoic acids, thus providing an appropriate net charge of the cell wall (Krawczyk-Balska et al 2012a; Krawczyk-Balska and Lipiak 2013).…”
Section: Cytoplasmic Proteins With Unknown Function Involved In the Rmentioning
confidence: 99%
“…Increased expression of mitochondrial ferritin provides new insights into the antioxidant role of ferritin in the brains of Alzheimer's disease (AD) patients [45]. A Listeria monocytogenes ferritin-like protein plays an essential role in acid stress tolerance [46][47]. Our study showed that ferritin plays an important role in the iron metabolic pathway of S. japonicum (Sup Figure 8).…”
Section: Discussionmentioning
confidence: 69%